Dataset associated with "Ocean Surface Flux Algorithm Effects on Tropical Indo-Pacific Intraseasonal Precipitation" - Hsu, Chia-Wei; DeMott, Charlotte; Branson, Mark (Colorado State University. Libraries, 2021)
Surface latent heat fluxes help maintain tropical intraseasonal precipitation. We develop a latent heat flux diagnostic that depicts how latent heat fluxes vary with the near-surface specific humidity vertical gradient (dq) and surface wind speed (|V|). Compared to fluxes estimated from |V| and dq measured at tropical moorings and the COARE3.0 algorithm, tropical latent heat fluxes in the NCAR CEMS2 and DOE E3SMv1 models are significantly overestimated at |V| and dq extrema. MJO sensitivity to surface flux algorithm is tested with offline and inline flux corrections. The offline correction adjusts model output fluxes toward mooring-estimated fluxes; the inline correction replaces the original bulk flux algorithm with the COARE3.0 algorithm in atmosphere-only simulations of each model. Both corrections reduce the latent heat flux feedback to intraseasonal precipitation, in better agreement with observations, suggesting that model-simulated fluxes are overly supportive for maintaining MJO convection.
This dataset is for ocean surface flux diagnostic and to reproduce the analyses and figures in the manuscript "Ocean Surface Flux Algorithm Effects on Tropical Indo-Pacific Intraseasonal Precipitation". The time period is from 1998 to 2014 and focus on the ocean region between 20S-20N and 90E-180.
Department of Atmospheric Science
Walter Scott, Jr. College of Engineering
Keywords: latent heat flux; precipitation; instraseasonal variation